Out of control: changes in working-time patterns and strategies for work-life balance in Europe. (1st April 2010) - Bettina-Johanna Krings; Linda Nierling; Marcello Pedaci
Abstract : Global restructuring processes mean that temporal models of working time are becoming increasingly differentiated across Europe, as elsewhere. In order to balance work and life, employees have to accommodate these changes, not necessarily by prolonging their working time, but through an accelerated pace of work and increased workloads. Intensified working time patterns increase the challenges of combining work and family. This paper argues that changing demands on working time have enormous impacts on establishing work-life balance and that – to a great extent – the consequences are shouldered by women. In assessing these changing demands on working time, it is crucial to consider the occupational context: a high level of autonomy in determining their working time as well as great dedication to their work provides women in highly-skilled occupations with the option of developing strategies for emancipation. Women working in semi-skilled and low-skilled occupations are more likely to adhere to traditional gender roles and suffer much more from externally-imposed temporal frameworks and organisational changes. These results underline the need to reflect on contextual categories such as occupational affiliation, skill-level, gender, and institutional settings in evaluating the individual impacts of the changing demands of working time and work-life balance across Europe.